COMPARATIVE CEPHALOMETRIC AND 3D CONE BEAM COMPUTED TOMOGRAPHY ANALISIS OF ALVEOLAR BONE DESTRUCTION FOR TEETH IN ANTERIOR CROSSBITE - Stilyana Krasteva; Silviya Krasteva; Konstantin Georgiev; Anzhelina Krasteva (Peytchinski Publishing, 2023)
Purpose: To assess the degree of bone destruction for teeth in anterior crossbite by means of 3D cone beam computed tomography and lateral cephalometry. Material/methods: 20 patients with anterior crossbite underwent 3D cone beam computed tomography and lateral cephalometry of the anterior segments of the maxilla and mandible. The destruction of the bone in the anterior segments of the maxilla and mandible was measured (vestibularly and lingually)- the distance from the cemento-enamel junction to the top of the alveolar bone. The parameters of bone resorption for teeth 21 and 31 on cephalogramsand 3D computed tomography images were compared. For both incisors, the mean value registered by means of cephalometry was slightly higher than that registered with 3D. Results: The total mean value of bone destruction for anterior teeth was significantly higher vestibularly compared to lingually, both for the maxilla (p = 0.030) and mandible (p = 0.030). Significantly higher mean values ​​of bone destruction were found in the mandible compared to the maxilla. For both incisors (21 and 31), the mean value of resorption recorded by cephalometry was slightly higher than that recorded by 3D cone beam computed tomography, but without statistical significance. Conclusion: We found significantly higher values ​​of vestibular bone destruction compared to lingual bone destruction. Bone destruction in the mandible reached a significantly higher level than that in the maxilla. No statistically significant difference was found between the mean values ​​of bone destruction measured by means of cephalometry and 3D cone beam computed tomography.